EMPLOYMENT POLICY IN INDONESIA FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Akmal, M. Irsyadu Robbi; Fatimah, Fatimah; Jihan, Sabrina Aura (Journal of Finance, Economics and Business, 2024)
The government has an important role in employment which influences the development of the country and its economy. Unfortunately, Indonesia has a lot of demand and supply for employment, especially regarding wage levels. This research aims to explain comprehensively about employment through data analysis, describing the problems that exist in Indonesia, where our country is famous for its culture and religion, however, besides that, the policies that occur in Indonesia often change, Therefore, policies must be maintained with real attention to targets. Labor is a person's obligation to do something on the orders of a superior to achieve a goal, so the agency must pay attention to labor wages in order to achieve expectations, apart from being a guarantee of labor, wages are also a reward given by the employer to its workers, the policy between employment and the wages they achieve. must be truly equivalent to what is being done. Labor in Islam is an effort that is carried out continuously to achieve a hope.